2020
DOI: 10.1101/2020.04.15.044115
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Toward a single dose cure for Buruli ulcer

Abstract: 25A single dose of TELACEBEC (Q203), a phase 2 clinical candidate for tuberculosis, eradicates 26 Mycobacterium ulcerans in a mouse model of Buruli ulcer infection without relapse up to 19 27 weeks post treatment. Clinical use of Q203 could dramatically simplify the clinical management 28 of Buruli ulcer, a neglected mycobacterial disease. 29 Text 30 Buruli ulcer is a chronic ulcerating disease of the skin and underlying tissues caused by 31 Mycobacterium ulcerans. The disease is regaining importance in West A… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Among new drugs, telacebec is promising in terms of potency, shorter duration (2 weeks) and tolerability in animal studies [64,[81][82][83]. In January 2021, telacebec was recognized as an orphan drug by US Food and Drug Administration.…”
Section: Buruli Ulcermentioning
confidence: 99%
“…Among new drugs, telacebec is promising in terms of potency, shorter duration (2 weeks) and tolerability in animal studies [64,[81][82][83]. In January 2021, telacebec was recognized as an orphan drug by US Food and Drug Administration.…”
Section: Buruli Ulcermentioning
confidence: 99%
“…Drug susceptibility testing against strains of the classical lineage showed hypersensitivity to Q203, with a minimum inhibitory concentration (MIC) value 10 times lower than that in M. tuberculosis (133). Additionally, Q203 was bactericidal against M. ulcerans both in vitro and in vivo (133,134). Importantly, Q203 demonstrated no sterilising effect against the ancestral lineage of M.…”
Section: Targeting the Terminal Oxidases Of M Tuberculosismentioning
confidence: 99%
“…In the context of the respiratory terminal oxidases in M. tuberculosis, combining chemical inhibition with genetic studies have clearly demonstrated the synthetic lethal relationship between the two terminal oxidases: Cyt-bcc:aa3 and Cyt-bd (75). The striking potency exhibited by Q203 (Telacebec) against M. ulcerans served as a precedent that the synthetic lethality of the two complexes could be exploited in M. tuberculosis (133,134). Given the abundance of antibacterials targeting Cyt-bcc:aa3, finding a small molecule inhibitor targeting Cyt-bd could improve the sterilising potency of many antibiotics against M. tuberculosis.…”
Section: Synthetic Lethalitymentioning
confidence: 99%
“…Q203 has also shown excellent potency against the NTM Mycobacterium ulcerans, the etiological agent of Buruli ulcer and is now considered a promising drug for the treatment of the disease (201,211).…”
Section: Introductionmentioning
confidence: 99%